Design and Manufacture of Elephant Grass and Palm Frond Chopping Machines - Romiyadi; Yudi Dwianda; Adi Febrianton; Purnama Irwan (Jurnal Teknik Mesin, 2022)
Elephant grass and palm frond chopping machines is a machine used to chop elephant grass and palm fronds for animal feed. The purpose of the study is to design and manufacture a machine used for animal feed. This machine is designed and manufactured to chop elephant grass and palm fronds. Based on the results of the design and manufacture, a machine for chopping elephant grass and palm fronds for animal feed has been designed and manufactured. This machine uses a gasoline motor with a capacity of 5.5 HP. While the transmission system used is a pulley and belt transmission system. Based on the test results, the elephant grass and palm frond chopping machine can operate and function properly. The test results also show that the volume of chopped elephant grass is greater than the volume of chopped palm fronds. While the results of chopped elephant grass are better than the results of chopped palm fronds